Implementasi Integrasi Sains dalam Pembelajaran Fikih di MAN 2 Mataram - Syamsul Arifin; Nur Hayati Mufida (LP2M STIT Palapa Nusantara, 2023)
This study aims to describe the practice of science integration in Fikih learning starting from the planning, implementation, and evaluation stages at MAN 2 Mataram. To achieve these objectives, this research uses a qualitative approach with a descriptive-phenomenological nature and the researcher acts as a key instrument. Data collection techniques were carried out by means of literature review of textbooks and LKS, observation of learning activities, in-depth interviews about learning, and documentation regarding learning tools. This study obtained the following results 1) the implementation of science integration in the three stages of Jurisprudence learning is maximally carried out on subjects with circular patterns, while those with linear patterns, let alone parallels, are not very optimal; 2) Science integration is carried out based on formal and non-formal curricula or hidden curricullum specifically on circular subjects and only based on non-formal curricula specifically on linear subjects; 3) The type of science integration applied is semipermeable with four models; a) informative; b) confirmative; c) similarisation, and d) complementation; 4) In this science integration practice, madrasah teachers experience confusion and dilemma because there is no educational regulation governing science integration in learning. Therefore, to improve the quality of science integration practices in Islamic science learning, there needs to be regulations and supporting learning tools made by the Ministry of Religious Affairs.